IBADAH EKPRESIF PADA GEREJA PROTESTAN - Agus Budi Handoko (TANGKOLEH PUTAI, 2019)
Expressive worship as a form of creative worship gives more room for congregants to be able to express feelings or emotions more as a form of expression of faith in worship. The use of expressive worship is still relatively new as a form of liturgical worship within the Protestan churches in the city of Palangka Raya. The purpose of this study is to explain the use of expressive worship and its impact on Sunday worship in the GKE of the Sakatik Congregation - Palangka Raya. Expressive worship in the Protestant church in this study that is used as an example is the GKE Sakatik, expressive liturgy arranged and held to try to be a more interesting and lively liturgy by encouraging congregations to be able to accentuate their expressions compared to regular worship. The liturgical liturgy is almost the same but what distinguishes it is the liturgical form which is not absolutely fixed looking at the liturgical arrangements that have been provided, the selection of songs that are adapted to developments, and the use of band music to accompany worship. In expressive worship the congregation praises and glorifies the name of God with various forms of expression, such as when praising God there are those who raise their hands, some who clap, some dance, some jump, and so on.